Globalization and Democratic Experiments: a Sociological Profiling of Nigeria’s Democratic Colonialism (1999-2015) (Glocalism: Journal of Culture, Politics and Innovation, 2016)
Globalization has become a contagious phenomenon that has not spared any society and social institutions. Events happening at the global arena has far-reaching impact and implications at the remotest village in virtually any part of the earth. The tidal wave of democracy as the most acceptable system of government and capitalism as the best economic system synchronized with the shattering hurricane of globalization around the world has been producing innumerable political changes. Nigeria like most countries in the third word that were formerly under military rule embraced the civilian rule in 1999 after 16 years of its suspension from 1983-1999. From this point of view this paper will seek to know the meaning of globalization, democracy and the inverse relationship of the two concepts on most of the third world countries in general and Nigeria in particular. A conceptual clarification of globalization and democracy will follow next. Methodologically, the paper adopted a qualitative methods of content analysis to analysed the literature and empirical studies on topic reviewed and provided some insightful sociological analyses and conclusions.
Keywords: Nigeria; democracy; globalization; colonialism; sociological analysis